2021
DOI: 10.1136/bmjopen-2021-053992
|View full text |Cite
|
Sign up to set email alerts
|

Health and social interventions to restore physical function of older adults post-hip fracture: a scoping review

Abstract: ObjectivesDespite inpatient rehabilitation, many older adults post-hip fracture have difficulty returning to their prefracture levels of function and activity. This scoping review aims to identify interventions for community-dwelling older adults discharged from inpatient rehabilitation and examine the function and activity outcomes associated with these interventions.DesignThis scoping review followed Arksey and O’Malley’s five-stage framework.Data sourcesWe searched MEDLINE, CINAHL, PsycINFO, EMBASE and Agel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…or therapists, or enhancing support from family and friends should be considered. 7 We also recommend focusing on patients with poor and declining social support not only because scores for outcomes of physical function and HRQoL were low, but also because these patients had low scores for nutritional status and high scores for depressive symptoms, which are often overlooked. Appropriate geriatric psychiatric interventions could reduce depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…or therapists, or enhancing support from family and friends should be considered. 7 We also recommend focusing on patients with poor and declining social support not only because scores for outcomes of physical function and HRQoL were low, but also because these patients had low scores for nutritional status and high scores for depressive symptoms, which are often overlooked. Appropriate geriatric psychiatric interventions could reduce depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…5 One study reported patients with hip fracture who received a 12-month intervention of high-intensity weightlifting exercises with social support following hospital discharge had lower mortality, fewer nursing home admissions, and less dependency in activities of daily living (ADLs) than those receiving usual care. 6 Auais et al 5 and Omar et al 7 noted a lack of studies on social support and outcomes for patients with hip fracture, with existing studies averaging only 12 months for follow-up, while there is some evidence that patients may experience declines in ADLs and physical functions beyond 1 year after hip-fracture surgery. 8,9 A scoping review of 24 studies on interventions for older adults following hospital discharge contained only three studies that examined social interventions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations